The effects of hybrid pay incentives on work-team performance: A longitudinal study - Mbusi Dlamini; Margie Sutherland; Merle Werbeloff (South African Journal of Economic and Management Sciences, 2015)
Despite the widespread use of pay incentives to drive performance, few studies empirically demonstrate their long-term benefits within work-team settings in field studies; even fewer studies incorporate hybrid pay incentives in their design. This longitudinal field study explored the effects on individual work performance of allocating tellers to teams with supervisors who received hybrid pay incentives, where 60 per cent of their incentive was based on the individual performance of each of their team members and 40 per cent on their own performance. It was conducted on bulk-cash tellers working in 19 centres, using a time-series design. The results, derived from quantitative data collected from 82 individual tellers over 24 months, showed that hybrid pay incentives for supervisors of teams of tellers, some of whom were individually incentivised, were associated with significant increases in the volume, speed and accuracy of deposit processing by all the tellers. The findings empirically demonstrate the long term sustainability of improved performance associated with the introduction of hybrid pay incentive structures within work teams.